Urban and rural primary school pupils' conceptions about the respiratory system and smoking - Tracana, Rosa Branca (2012)
An important objective of primary school teaching is to make children learn scientific contents. For this, teachers must know their pupils’ previous ideas in order to provoke effective conceptual changes. We analysed primary school pupils’ conceptions and their learning difficulties by carrying out a cross-sectional study. Five to 9 years old pupils’ conceptions about respiration and smoking were analysed before the first formal teaching of the topic and immediately after teaching and one year after. We focused on the anatomo-physiology of the respiratory tract as well as on the unhealthy effects of smoking. The aim was to identify not only patterns of children’s previous ideas about breathing and smoking unhealthy effects but also epistemological and didactical obstacles to learning. Several patterns on the passage of tobacco in the smoker’s body were created from children’s drawings before teaching. Significant differences (p<0.05) between urban and rural schools as well as between sub-samples of either urban or rural schools were found. After formal teaching, about 90% of 3rd and 4th year pupils represented the correct anatomo-physiology of the respiratory tract (p<0.05). However, no significant differences about smoking effects were found (p>0.05). The patterns of children’s previous ideas about breathing and smoking and the didactical obstacles identified in the present study may be an important contribute for teachers to use them in the process of pupils’ conceptual change.